KEBIJAKAN PENINGKATAN IKLIM KERJA DI SD SE-KECAMATAN KESAMBEN - Soebiantoro Soebiantoro (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
This study is a correlational study seeing the relationship between work condition and teacher ’s performance in teaching. The study uses 61 respondents in SDs of Kesamben. Product Moment correlation was used to analyze the data. The findings of the study indicated that a significant correlation was obtained. Statistical testing showed that the work condition (X) has positive relationship to the teacher ’s performance (Y) at p=0.005 and df = 16. Relying on the r-value 0.803, Ho of this study was rejected since r-table was lower (0.254). This means work condicition has significant relationship to teacher ’s performance, implying that the better the work atmosphere is the better the teacher performance at school.